LEARNING OBJECTS AND INTERACTIVE WHITEBOARDS: A EVALUATION PROPOSAL OF LEARNING OBJECTS FOR MATHEMATICS TEACHING - Fiscarelli, Silvio Henrique [UNESP]; Morgado, Camila Lourenco [UNESP]; Felix, Monique Alves [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The current conditions of the classroom learning tend to be a one-way process based in teacher exposition, this make a negative impact on learning make it a mechanical and not meaningful activity. One possibility to improve the quality of teaching is to innovate methodologies and varying forms of presenting information to students, such as the use of technology in the teaching process. The Interactive Whiteboard (IBW) is one of the technologies that are being implemented in Brazilian schools. One of the promising possibilities to add value to the use of LDI in classroom are learning objects (LO). However, one problem is that often the LO are not fully suited to the dynamics of IWB, whether functional or pedagogical point of view. The objective of this study is to analyze and propose a set of indicators that evaluate the learning objects for use in conjunction with Interactive Whiteboards. The selection and definition of evaluation indicators was carried from the literature review on the subject and based on LDI experiences of use in Municipal Elementary School. After defining the set of indicators was conducted a evaluation of a sample of 30 OA utilized to teaching mathematics in 3rd grade of elementary school. The results of the evaluation indicate that the proposed indicators are suitable for a pre-analysis of OA and assisting in the process of selection of these.
Keywords: Technology; Learning objects; Digital whiteboards; Software evaluation; Indicators